2020
DOI: 10.21203/rs.3.rs-23417/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A health care record review of early mobility activities after fragility hip fracture: Utilizing the French systematic method to inform future interventions

Abstract: BackgroundA fragility hip fracture is a serious injury in older adults. After experiencing a fracture, a large percentage of patients do not regain their pre-fracture level of mobility. There are several international guidelines recommending early mobility after surgery. We do not know the usage of these early mobility recommendations by health care providers within our institution. An evidence-to-practice gap occurs when there is a failure to implement best practices. Utilization of a systematic method allows… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The hospital admits approximately 200 older adults with hip fracture per year [ 14 ]. As per Health Quality Ontario (HQO) recommendations [ 15 ], surgical repair of a fragility hip fracture occurs within 48 h of patient admission [ 10 ]. The main case was purposefully selected as the unit where most patients after hip fracture surgery are admitted, as this unit had previously implemented hip fracture recommendations in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital admits approximately 200 older adults with hip fracture per year [ 14 ]. As per Health Quality Ontario (HQO) recommendations [ 15 ], surgical repair of a fragility hip fracture occurs within 48 h of patient admission [ 10 ]. The main case was purposefully selected as the unit where most patients after hip fracture surgery are admitted, as this unit had previously implemented hip fracture recommendations in 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The Hip Fracture Care & Toolkit was designed to standardize and disseminate hip fracture best practices across the continuum of care in all Canadian provinces [ 6 ]. A recent chart review of the older adult hip fracture population on this unit [ 10 ] identified that early mobility activities are initiated in the first five days after surgery to varying degrees. Many patients did not participate in early mobility activities, with non-participation rates higher in those with a low pre-fracture functional mobility level and those with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%